Phosphorus uptake kinetics of Acinetobacter in activated sludge mixed liquor - Cloete, T.E. (Thomas Eugene), 1958- (University of Pretoria, 2022)
Dissertation (MSc (Microbiology))--University of Pretoria, 1992.